2017
DOI: 10.1111/lam.12718
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and bioprospecting of actinomycete endophytes from the medicinal plants

Abstract: Significance and Impact of the Study: "Endophytes" -the microbes residing in the living tissues of plants are virtually omnipresent. Actinomycete endophytes are diverse in distribution within plant tissues, especially in the roots as they have a close association with the rhizhosphere. An introspection into diversity studies necessitates careful sampling, analysis, and isolation data from the biodiverse and nonbiodiverse regions represented by unique environments. The key to the recovery of novel species and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 69 publications
1
30
0
2
Order By: Relevance
“…The highest number of isolated strains obtained from roots (n = 65, 45.5 %), followed by stems (n = 41, 28.7 %) and leaves (n = 37, 25.9 %) ( Figure 2a). This result was similar to recent studies showing that the number of actinomycetes isolated from roots was regularly higher than that from stems and leaves [11,12,13]. Studies on diversity of actinobacteria residing in medicinal plants based on morphology and amino acid composition of the whole-cell extract the percentage of endophytic actinobacteria recovered from different explants, Taechowisan et al, 2003 [14] found 64.2 % isolates from roots, 29.4 % from leaves, and 6.4 % from stems of 36 different plant species.…”
Section: Distribution Of Endophytic Actinomycetes On Different Parts supporting
confidence: 92%
See 2 more Smart Citations
“…The highest number of isolated strains obtained from roots (n = 65, 45.5 %), followed by stems (n = 41, 28.7 %) and leaves (n = 37, 25.9 %) ( Figure 2a). This result was similar to recent studies showing that the number of actinomycetes isolated from roots was regularly higher than that from stems and leaves [11,12,13]. Studies on diversity of actinobacteria residing in medicinal plants based on morphology and amino acid composition of the whole-cell extract the percentage of endophytic actinobacteria recovered from different explants, Taechowisan et al, 2003 [14] found 64.2 % isolates from roots, 29.4 % from leaves, and 6.4 % from stems of 36 different plant species.…”
Section: Distribution Of Endophytic Actinomycetes On Different Parts supporting
confidence: 92%
“…As showed in Figure 1, a wide variety of colony morphologies and mycelium colours was observed in all endophytic actinomycetes. Numerous studies indicated that species distribution and biological diversity of endophytic actinobacteria of medicinal plants are extensively influenced by isolation methods, plant species and sampling geographical area [11]. Gangwar et al, 2014 [12] successful isolated 40 actinomycetes strains from roots, stems, and leaves of Aloe vera, Mentha sp.…”
Section: Isolation and Distribution Of Endophytic Actinomycetes From mentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, many Streptomyces have been isolated from traditional plant medicines, especially in areas of low nutrient availability or extreme physiological conditions [27,28]. These Streptomyces can exist as endophytes that live at least a part of their life cycle inside plant tissues without causing damage, or epiphytes that live on the outside of the plants [29,30]. Proteobacteria and Actinobacteria have been reported as the most frequent endophytic species [31].…”
Section: Streptomyces From Traditional Medicinal Plantsmentioning
confidence: 99%
“…Endophytic bacteria, especially those belonging to the actinomycetes group, are an important yet underdeveloped microbial resource for novel natural products ( 1 4 ). As part of a larger research project aimed at discovering new biologically active compounds from endophytic actinomycetes, we isolated Streptomyces sp.…”
Section: Genome Announcementmentioning
confidence: 99%